Challenging online situations reported by Italian and Portuguese children in 2018 - Cristina Ponte (Revista Mediterránea de Comunicación)
Based on the results of the EU Kids Online survey (2018) already completed in Portugal and Italy, this article analyses two issues related to the growing dissemination of hate messages and fake news:  firstly, how Italian and Portuguese children and young people aged 9-17 are coping with negative online content and conduct. Secondly, how they report their informational skills and their relationship with the news content. In comparison to previous surveys conducted in both countries (EU Kids Online 2010, Net Children Go Mobile, 2014), the results reveal an increase in negative online experiences – such as exposure to hate messages, to violent and gory images, or being the victim or perpetrator of cyberbullying. Although the levels of troubling experiences are much higher in Portugal, Italian and Portuguese children present relatively similar patterns of coping. In both countries, informational skills relating to surfing or searching for accurate information are reported much less frequently than technological or social digital skills. Gender is significant in these two issues as well as age. These results underline the need for empowering children with human values and critical literacy, as part of a culture of digital rights and responsibilities.